Fibroblast growth factor receptor signaling in cardiomyocytes is protective in the acute phase following ischemia-reperfusion injury - Matsiukevich, Dzmitry; House, Stacey L.; Weinheimer, Carla; Kovacs, Attila; Ornitz, David M. (Frontiers in Cardiovascular Medicine, 2022)
Fibroblast growth factor receptors (FGFRs) are expressed in multiple cell types in the adult heart. Previous studies have shown a cardioprotective effect of some FGF ligands in cardiac ischemia-reperfusion (I/R) injury and a protective role for endothelial FGFRs in post-ischemic vascular remodeling. To determine the direct role FGFR signaling in cardiomyocytes in acute cardiac I/R injury, we inactivated Fgfr1 and Fgfr2 (CM-DCKO) or activated FGFR1 (CM-caFGFR1) in cardiomyocytes in adult mice prior to I/R injury. In the absence of injury, inactivation of Fgfr1 and Fgfr2 in adult cardiomyocytes had no effect on cardiac morphometry or function. When subjected to I/R injury, compared to controls CM-DCKO mice had significantly increased myocyte death 1 day after reperfusion, and increased infarct size, cardiac dysfunction, and myocyte hypertrophy 7 days after reperfusion. No genotype-dependent effect was observed on post-ischemic cardiomyocyte cross-sectional area and vessel density in areas remote to infarct. By contrast, constitutive activation of FGFR1 signaling in cardiomyocytes just prior to the onset of ischemia did not affect outcomes after cardiac I/R injury at 1 day and 7 days after reperfusion. These data demonstrate that cell-autonomous cardiomyocyte FGFR signaling is required for acute recovery from cardiac I/R injury and that endogenous activation of FGFR1 signaling in cardiomyocytes is sufficient to provide acute cardioprotection, which results in continued improved outcomes during cardiac remodeling. Combined with the established protective role of some FGF ligands and endothelial FGFR signaling in I/R injury, this study supports the development of therapeutic FGFs for acute I/R injury.